The Predictive Value of Coronary Artery Disease Complexity for Adverse Clinical Events and Myocardial Injury in Patients with Acute Coronary Syndrome - Durmaz, Eser; Karadağ, Bilgehan; İkitimur, Barış and Kılıçkıran Avcı, Burçak and Yurtseven, Ece and Barman, Hasan Ali and Ertuğrul, Sait and Ertürk, Emre and Koldaş, Lale (Cerrahpaşa Medical Journal, 2020)
Objective: The complexity of coronary artery disease (CAD) poses a challenge during percutaneous coronary interventions. Although it is well-defined in patients with stable ischemic heart disease, its prognostic implication and effect on myocardial injury are not demonstrated well in patients with acute coronary syndrome (ACS). Methods: We enrolled 313 patients with ACS (149 ST-elevated myocardial infarction and 164 ACS without ST elevation) in this study. The complexity of CAD was decided using SYNTAX score (SxS). Amount of myocardial injury was determined according to high-sensitive troponin and creatine-kinase levels. Clinical outcomes were reinfarction, revascularization, and cardiac death. Results: Thrombolysis in myocardial infarction and global registry of acute coronary events risk scores were significantly higher in patients with high SxS (p=0.007 and p<0.001, respectively). There was no significant difference in cardiac biomarkers (p=0.429 for troponin and p=0.253 for creatinine kinase myocardial band). Ejection fraction was significantly lower in patients with high SxS (p=0.006). Clinical endpoints were similar between syntax groups (p=0.402 for reinfarction and p=0.342 for cardiac death) except revascularization. Revascularization was higher in patients with high SxS (p=0.007). When patients in ST-segment elevated myocardial infarction and non–ST-segment elevated myocardial infarction/unstable angina pectoris groups were examined together, clinical endpoints were significantly higher in the high SxS group. Conclusion: Our study demonstrated that the complexity of CAD in patients with ACS is associated with adverse clinical outcomes but not with myocardial injury. Cite this article as: Durmaz E, Karadağ B, İkitimur B, Kılıçkıran Avcı B, Yurtseven E, Barman HA, et al. The Predictive Value of Coronary Artery Disease Complexity for Adverse Clinical Events and Myocardial Injury in Patients with Acute Coronary Syndrome. Cerrahpaşa Medical Journal 2020; 44(2): 74-79.